The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1109/tmtt.2002.807687
|View full text |Cite
|
Sign up to set email alerts
|

Transient characteristics of gan-based heterostructure field-effect transistors

Abstract: A triple-band dipole antenna with wideband balun integration is proposed in this article. This antenna consists of two dipoles, a wideband balun and feeding line. These three parts are integrated into a compact design, which has a small size of 30 Â 25 Â 0.8 mm 3 based on the substrate having a dielectric constant of 2.55. The simulated results show that triple bands of 2.40-2.59 GHz, 3.42-3.80 GHz, and 5.06-5.95 GHz are attained by this antenna, and can cover the bands of WLAN/WiMAX. The simulated and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…7 and 10). The time constant (∼0.1 s) is the RC charging/discharging time [39] or the transit time that it takes for an electron to reach the traps that are deep in the buffer. In fact, Binari et al ascribed the current collapse induced by a high current and a high V DS pulse to the trapping in the buffer [3], which is consistent with our result.…”
Section: B Detrapping Behaviormentioning
confidence: 99%
“…7 and 10). The time constant (∼0.1 s) is the RC charging/discharging time [39] or the transit time that it takes for an electron to reach the traps that are deep in the buffer. In fact, Binari et al ascribed the current collapse induced by a high current and a high V DS pulse to the trapping in the buffer [3], which is consistent with our result.…”
Section: B Detrapping Behaviormentioning
confidence: 99%
“…͓DOI: 10.1063/1.2798500͔ AlGaN / GaN heterostructure field-effect transistors ͑HFETs͒ have been the subject of intense investigation due to their importance for microwave and high temperature/high power applications. 1,2 The mobility of electrons in the twodimensional electron gas ͑2DEG͒ channel is crucial to the ultimate performance of an AlGaN / GaN HFET. It has been shown that electron mobility is dominated by optical phonon scattering or possibly interface roughness scattering at room temperature.…”
Section: Electron Mobility Related To Scattering Caused By the Strainmentioning
confidence: 99%
“…Al x Ga 1-x N/GaN heterostructure have a large band offset, large polarization effect [1] high two-dimensional electron gas densities, and a high saturation electron drift velocity [2][3][4][5][6][7][8][9] that makes them suitable for many microelectronic applications.…”
Section: Introductionmentioning
confidence: 99%